2009
DOI: 10.1016/j.bbrc.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of neuronal and inducible nitric oxide synthase (NOS) in the spinal cord of mutant SOD1 (G93A) ALS mice

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a fatal neurological disorder characterized by degeneration of motor neurons throughout the central nervous system. Mutations of the free radical scavenging enzyme superoxide dismutase-1 (SOD1) are a cause of familial ALS but it is not known how mutations lead to cell death. Free radicals such as nitric oxide (NO) are thought to play a key pathogenic role. NO is synthesized by NO synthases (NOSs) from arginine, which is a rate-limiting factor for NO production. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…This indicates that the iNOS expression was not induced by a T cell-mediated pathway. This unique iNOS expression pattern is similar to that reported in ALS patients [16,18] and SOD1-transgenic mice [1,11]. The absence of inflammatory T-cells from the present cases may indicate that abnormal glial iNOS expression in the spinal gray matter is a primary factor in the pathogenesis of canine DM.…”
Section: Discussionsupporting
confidence: 87%
“…This indicates that the iNOS expression was not induced by a T cell-mediated pathway. This unique iNOS expression pattern is similar to that reported in ALS patients [16,18] and SOD1-transgenic mice [1,11]. The absence of inflammatory T-cells from the present cases may indicate that abnormal glial iNOS expression in the spinal gray matter is a primary factor in the pathogenesis of canine DM.…”
Section: Discussionsupporting
confidence: 87%
“…Differential NOS sources and expression time courses have been attributed to the number of expressed mutant SOD1 G93A copies in animal models [166] and/or the specificity of nNOS antibodies used [167]. Some of the work [167][168][169] was performed in SOD1 G93A mice expressing a low copy number (∌10 copies; SOD1 G93A-low ) of the transgene, with later onset and slower disease progression than in transgenic mice expressing a high copy number (∌20 copies; SOD1 G93A-high ) of the mutant SOD1 G93A [90,166,[170][171][172]. Relative to the iNOS isoform, the time course of its upregulation and gliosis in spinal cord paralleled that of motor neuronal loss in transgenic SOD1 G93A-high mice.…”
Section: Als Patientsmentioning
confidence: 99%
“…Relative to the iNOS isoform, the time course of its upregulation and gliosis in spinal cord paralleled that of motor neuronal loss in transgenic SOD1 G93A-high mice. Two studies have shown the presence of numerous highly iNOSir cells with the appearance of glial cells, but not in neurons, at early-symptomatic and end stages of disease, but not in asymptomatic mice [170,171]. On the other hand, the presence of iNOS mRNA in the spinal cord and brainstem motor regions has been reported using RT-PCR in SOD1 G93A mice and increased in pre-symptomatic (<P70) and early-symptomatic (P70-P91) stages [166,170].…”
Section: Als Patientsmentioning
confidence: 99%
“…Further, NO has been shown to be cytotoxic in ALS animal models [111,112]. In the spinal cord of SOD1 G93A ALS mice, the net amount of NO and citrulline was increased [113] due to an induced inducible NOS (iNOS) expression in astrocytes, whilst nNOS expression was significantly reduced in motor neurons of SOD1 G93A ALS mice. The time course of spinal cord gliosis and iNOS up-regulation is parallel to motor neuronal loss in transgenic mutant SOD1 mice [111].…”
Section: Calmodulin and The Ca 2+ /Calmodulin-dependent Protein Kinasesmentioning
confidence: 99%